SEKAPUR SIRIH AN-NAJAH ENGLISH COURSE DI YAYASAN PENDIDIKAN AN-NAJAH ISLAMIC MODERN EDUCATION CENTER DALAM PEMBELAJARAN KOSAKATA DENGAN MEDIA PUZZLE - Nency Dela Oktora (JURNAL PENGABDIAN MANDIRI, 2022)
For young learners, learning English, especially vocabulary, has its own challenges. It can be seen from the lack of vocabulary skills for young learners found in schools. The basis of English language learning is vocabulary. Students may not communicate their ideas in oral or written form without vocabulary. So, it is not possible to underestimate teaching vocabulary for young learners and must be particular concern. In this way, the use of learning media is very important in order to reach learning goals, not only as a means of encouragement but as a priority. The use of puzzle media will help teachers provide vocabulary content in the classroom. This community service activity is located at An-Najah English Course Sambikarto, Sekampung, East Lampung. The result of teaching using puzzle media showed a significant impact in improving students’ English vocabulary mastery skills.